Avaliação da mobilidade urbana da zona central do município de Pato Branco (PR) no acesso de serviços essenciais sob a ótica do conceito cidade de 15 minutos - Molinete, Heloisa Balbinotti (2024)
There is a need to look for urban planning models that focus on the population, which improve the community's quality of life through the proximity and accessibility of essential basic services in a short space of time, preferably using active transportation. The aim of this study was to evaluate urban mobility in the central area of the municipality of Pato Branco (PR) in terms of access to essential services from the perspective of the “15-minute city” concept. The working method consisted of a field survey of the conditions of the structure and conservation of sidewalks in the central area of the municipality. This was followed by mapping the essential services covered by the city's urban perimeter. Finally, using 15-minute isochrones generated in QGIS software, accessibility was assessed, identifying areas with poor access and distribution of public facilities and services. The conclusion is that the method used was adequate, as it allowed for good analysis by category and/or service. When considering only the accessibility of services within a 15-minute walk, the results show that the Jardim das Américas, Brasília, Amadori, Baixada, Centro, Trevo da Guarani, Sambugaro and São Vicente neighborhoods stood out. Furthermore, when evaluating only infrastructure conditions, the best-rated neighborhoods were Jardim das Américas, Baixada and Centro, Parzianello, Amadori and Santa Terezinha. Therefore, the neighborhoods of Centro, Baixada and Jardim das Américas stood out positively both in the analysis of infrastructure and accessibility within 15 minutes.